Income Hedging, Dynamic Style Preferences, and Return Predictability - ADDOUM, JAWAD M.; DELIKOURAS, STEFANOS; KORNIOTIS, GEORGE M.; KUMAR, ALOK (Journal of Finance, 2019)
ABSTRACT We propose a theoretical measure of income hedging demand and show that it affects asset prices. We focus on the value factor and first demonstrate that our demand estimates are correlated with the actual demands of retail and mutual fund investors. We then show that the aggregate high‐minus‐low (HML) demand predicts HML returns. Exploiting the state‐level variation in income risk, we demonstrate that state‐level hedging demands predict state‐level HML returns. A long‐short portfolio that exploits this hedging‐induced predictability earns an annualized risk‐adjusted return of 6%.